The Effect of Leadership Style on the Job Satisfaction of Micro and Small Enterprises - Zerihun Ayenew Birbirsa; Deresse Mersha Lakew (Universitas Prasetiya Mulya, 2020)
The major factors that determine both success and failure of Small Business include substantive and legitimate, learning strategies and leadership behaviors that may be among the principal reasons why some small businesses succeed while others fail to understand the learning strategies, leadership knowledge, and skills used by successful small business leaders (SSBLs). The objective of the study is to reveal out the relationship between leadership style and job satisfaction of MSEs at western oromia, Ethiopia.Stratified random sampling was used to get information from different sizes of the MSEs. selected from Manufacturing, service, agriculture, construction and trade sectors on proportional basis. Accordingly, 334 respondents were selected from the total of 1931 MSEs. Finally, the study revealed out that that there is statistically significant relationship between leadership style and job satisfaction. Also, the more exercising transformational leadership style, there would be more possibility of enhancing level of job satisfaction of MSEs.Keywords:Leadership style, Transactional, Transformational, Charismatic, Job satisfaction, Micro and Small Enterprises* Department of Management, Jimma University, PO box 378, Jimma University, Jimma, Ethiopia https://doi.org/10.21632/irjbs.13.1.27-32